Distribution of functional groups in periodic mesoporous organosilica materials studied by small-angle neutron scattering with in situ adsorption of nitrogen - Sharifi, Monir; Wallacher, Dirk; Wark, Michael (Beilstein Journal of Nanotechnology, 2012)
Periodic mesoporous materials of the type (R′O)3Si-R-Si(OR′)3 with benzene as an organic bridge and a crystal-like periodicity within the pore walls were functionalized with SO3H or SO3− groups and investigated by small-angle neutron scattering (SANS) with in situ nitrogen adsorption at 77 K. If N2 is adsorbed in the pores the SANS measurements show a complete matching of all of the diffraction signals that are caused by the long-range ordering of the mesopores in the benzene-PMO, due to the fact that the benzene-PMO walls possess a neutron scattering length density (SLD) similar to that of nitrogen in the condensed state. However, signals at higher q-values (>1 1/Å) are not affected with respect to their SANS intensity, even after complete pore filling, confirming the assumption of a crystal-like periodicity within the PMO material walls due to π–π interactions between the organic bridges. The SLD of pristine benzene-PMO was altered by functionalizing the surface with different amounts of SO3H-groups, using the grafting method. For a low degree of functionalization (0.81 mmol SO3H·g−1) and/or an inhomogeneous distribution of the SO3H-groups, the SLD changes only negligibly, and thus, complete contrast matching is still found. However, for higher amounts of SO3H-groups (1.65 mmol SO3H·g−1) being present in the mesopores, complete matching of the neutron diffraction signals is no longer observed proving that homogeneously distributed SO3H-groups on the inner pore walls of the benzene-PMO alter the SLD in a way that it no longer fits to the SLD of the condensed N2.
Keywords: contrast matching; crystal-like periodicity; distribution of functional groups; PMO; SANS; surface functionalization